Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/humu.24255
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of HLA‐I LOH in Chinese pan‐cancer patients and genomic features of patients harboring HLA‐I LOH

Abstract: HLA‐I LOH may facilitate immune evasion. However, large population studies on the prevalence of HLA‐I LOH across different cancer types and in relation to mutational profiles are lacking, in particular, in the Chinese population. In this study, analysis was performed in 1504 advanced pan‐cancer patients and 134 early‐stage non‐small‐cell lung cancer patients using a 1021‐gene panel. The consistency between the 1021‐gene panel and whole‐exome sequencing was evaluated in 45 samples, where concordant results were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…(Figures 1B,C and Supplementary Table S1). The frequency of HLA LOH in lung adenocarcinomas (LUAD) was lower than in lung squamous cell carcinomas (LUSC) (Figure 1D), which was consistent with previous studies (Zhao et al, 2021).…”
Section: Genomics Characteristics Of Chinese Lung Patients With Diffe...supporting
confidence: 92%
See 2 more Smart Citations
“…(Figures 1B,C and Supplementary Table S1). The frequency of HLA LOH in lung adenocarcinomas (LUAD) was lower than in lung squamous cell carcinomas (LUSC) (Figure 1D), which was consistent with previous studies (Zhao et al, 2021).…”
Section: Genomics Characteristics Of Chinese Lung Patients With Diffe...supporting
confidence: 92%
“…Compared with LUAD, the frequency of HLA LOH in LUSC was higher, which suggested that HLA LOH may have different effects on the efficacy of ICIs in LUAD and LUSC ( Zhao et al, 2021 ). Therefore, the predictive effect of HLA LOH on immunotherapy in NSCLC with different pathological classifications was further analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, anti-tumor immunity of LUAD patients (15)(16)(17), tumor immunogenicity (5, 6, 10-12, 16, 18-20), and tumor immune microenvironment (TME) (7,11,14,18,19,21) are also reported to modulate the therapeutic impact of ICIs. Several biomarkers, including tumor mutational burden (TMB) (11), blood tumor mutational burden (bTMB) (22), human leukocyte antigens (HLA) loss-of-heterozygosity (LOH) status (20), and murine double minute 2/4 (MDM2/ MDM4) amplification (23), which could affect the adaptive immune response to the tumors, have been widely studied to be associated with the efficacy of ICI therapy in LUAD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the proportion of the C3 inflammatory IS (179 patients, 39.2%) was the most common IS observed in the TCGA LUAD cohort, whereas C1 was particularly dominant in LUSC (273 patients, 57.1%). Other ISs were less commonly encountered in the TCGA NSCLC cohort, such as the C1 Wound healing (83 patients, 18.2%), C4 Lymphocyte depleted(20…”
mentioning
confidence: 99%